2021
DOI: 10.3390/molecules26041069
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals of Conocarpus spp. as a Natural and Safe Source of Phenolic Compounds and Antioxidants

Abstract: Optimization of the extraction conditions of polyphenolic compounds for different parts of the Damas species, Conocarpus lancifolius and Conocarpus erectus, grown under UAE conditions was studied. The combination of ethanol concentration (50, 75, and 100%), temperature (45, 55, and 65 °C) and time (1, 2, and 3 h) was used by applying the Response Surface Methodology. The data showed that the extracts (n = 90) contained phenolic compounds, flavonoids, and tannins, and were free of alkaloids. Changing the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
(42 reference statements)
3
13
0
1
Order By: Relevance
“…In this study, the active compounds (phenolic compounds, flavonoid, tannin, saponin, glycoside, gallic acid, apigenin, catechin, and quercetin) of C. erectus leaf meal were similar to previous studies that detected the phenolic compounds, saponins, flavonoids, and tannins in the aqueous and ethanolic extract of C. erectus (Afifi et al, 2021;Nascimento et al, 2016). Studies showed that various secondary metabolite components, such as saponins, tannins, alkaloids, phenolics, and flavonoids, are available in many parts of plants, particularly medicinal plants (Amal et al, 2009;Cutter, 2000), and are known to be antioxidants, antimicrobials, and anti-inflammatory (Ibrahim et al, 2006;Lo and Chung, 1999;Thompson and Collins, 2013;Wang et al, 2015;You et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the active compounds (phenolic compounds, flavonoid, tannin, saponin, glycoside, gallic acid, apigenin, catechin, and quercetin) of C. erectus leaf meal were similar to previous studies that detected the phenolic compounds, saponins, flavonoids, and tannins in the aqueous and ethanolic extract of C. erectus (Afifi et al, 2021;Nascimento et al, 2016). Studies showed that various secondary metabolite components, such as saponins, tannins, alkaloids, phenolics, and flavonoids, are available in many parts of plants, particularly medicinal plants (Amal et al, 2009;Cutter, 2000), and are known to be antioxidants, antimicrobials, and anti-inflammatory (Ibrahim et al, 2006;Lo and Chung, 1999;Thompson and Collins, 2013;Wang et al, 2015;You et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…L growing in Indonesia was lower than Trolox. It is in line with previous studies (26)(27)(28). The authors consider that the extracts are a mixture of several compounds.…”
Section: In Vitro Antioxidant Activity Judgmentsupporting
confidence: 91%
“…A higher extraction yield was observed in methanol extract (11.14 %), followed by chloroform extract (2.74 %) and n-hexane (1,74 %). It indicates that the extraction increases as the polarity of the solvent are used in the extraction process (26,27). Therefore, the higher percentage result in methanol extract might be related to the high polarity of the methanol solvent.…”
Section: The Flower Extract Of Averrhoa Bilimbi L Growing In Indonesiamentioning
confidence: 99%
“…For example, the study by Sivakavinesan et al 12 used peels of Garcinia mangostana (Mangostan) along with gold solution to prepare gold NPs and reported an improvement in color fastness of the copper-dyed fabrics. Another study by Afifi et al 13 reported that there are phenolic acids found in the plant extract and these may be used as reducing agents. Similarly, the Ghidan et al study reported the green synthesis of copper NPs (CuNPs) using Punica granatum peel extract.…”
Section: Introductionmentioning
confidence: 99%